CORRELATION AND PATH ANALYSIS IN CLUSTER BEAN [CYAMOPSIS TETRAGONOLOBA (L.) TAUB.] FOR VEGETABLE POD YIELD AND ITS COMPONENT CHARACTERS - SHEELA N. MALAGHAN; M. B. MADALAGERI; Y. K. KOTIKAL (The Bioscan, 2014)
An experiment was conducted on 67 cluster bean genotypes to study the correlation among the vegetable pod yield components and their direct and indirect effects on the vegetable pod yield. This study helps in identifying the characters which mainly contributing to vegetable pod yield. Correlation analysis indicated that vegetable pod yield per plant was significant and positively associated with pod length (cm) (0.399, 0.321), pod breadth (cm) (0.497, 0.338), ten fresh pods weight (g) (0.501, 0.351) and pods per plant (0.453, 0.655). Genotypic path coefficient analysis revealed that pod length (2.424) and pods per plant (1.210) exhibited positive direct effect and strong degree of association on vegetable pod yield per plant (0.399**, 0.453**) respectively. Phenotypic path coefficient shows that pods per plant (0.895), pod length (0.390), ten fresh pod weight (0.237) and pod breadth (0.110) had positive direct effect on vegetable pod yield per plant. Hence, this suggesting that the parameters viz., pods per plant, pod length, ten fresh pod weight and pod breadth may be considered as prime traits during the course of selection to have the higher potential of vegetable pod yields in case of cluster bean.